THE ROLE OF ECONOMIC GROWTH IN THE REDUCTION AND INCREASING OF UNEMPLOYMENT: A PERSPECTIVE ANALYSIS - Amien, Neneng Nurbaeti (2020)
Unemployment is one of the economic problems caused by an imbalance between the number of workers and the number of jobs available in a country or a region. This unemployment problem will have an impact on various aspects such as social, political, and economic growth. In Indonesia alone, the poverty and unemployment rates are increasing due to this pandemic. Even though the poverty target in 2020 is around 9.7% to 10.2%. As for 2021, the poverty target is also 9.2% - 9.7%. Meanwhile, the Gini ratio target in 2020 is around 0.379 to 0.381. Meanwhile, in 2021 it will be around 0.377 to 0.379. A large number of unemployed will be a major factor in hampering economic growth in Indonesia. The role of the government in this matter is very much needed, as is the improvement in the business field in Indonesia. This step may be of little help in reducing the number of unemployed, which is expected to increase every year. It is estimated that unemployment will increase this year due to the Covid 19 outbreak that has attacked countries in the world, including Indonesia.